Efektivitas model Home Visit dalam asuhan keperawatan gigi keluarga di Desa Peuniti, Banda Aceh - Reca, Reca; Salfiyadi, Teuku; Rahayu, Eka Sri; Nuraskin, Cut Aja; Febriani, Henny; Wirza, Wirza; Dzaki, Muhammad Haikal (Jurnal PADE: Pengabdian & Edukasi, 2025)
Peuniti Village is one of 10 villages in Baiturrahman District, Banda Aceh City, with diverse socio-cultural characteristics and a high prevalence of childhood dental caries. The initial survey showed that 85% of families experienced caries and children's dental hygiene was generally poor (PHP-M score = 38), far from government standards (<15). The purpose of this activity was to improve mothers' knowledge, attitudes, practices, and children's dental hygiene through the implementation of a home visit model of family dental nursing care. The method used was descriptive, targeting 60 children and their mothers as respondents. The intervention was conducted through three home visits over 21 days, with pre-test, post-test I, and post-test II evaluations. The results showed a significant increase in all indicators. Mothers' knowledge increased from sufficient to good (76,7%), mothers' attitudes from poor to good (80%), mothers' actions in assisting with tooth brushing from sufficient to good (83%), and children's dental hygiene status (PHP-M) from poor/very poor to good (93,3%) and very good (6,7%). This family-based educational approach has proven effective through interactive methods, demonstrations, and visual reinforcement. This activity also demonstrates the importance of mothers' roles as agents of change in children's dental care at home. In conclusion, the home visit model has proven effective in fostering healthy family behaviors independently. It is recommended for replication in other regions with cross-sectoral support to reduce caries rates preventively and sustainably